Plug-in Bandwidth Selection for Kernel Density Estimation with Discrete Data - Chi-Yang Chu; Daniel J. Henderson; Christopher F. Parmeter (Econometrics, 2015)
This paper proposes plug-in bandwidth selection for kernel density estimation with discrete data via minimization of mean summed square error. Simulation results show that the plug-in bandwidths perform well, relative to cross-validated bandwidths, in non-uniform designs. We further find that plug-in bandwidths are relatively small. Several empirical examples show that the plug-in bandwidths are typically similar in magnitude to their cross-validated counterparts.